The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/polym15030727
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pavement Material Using Crumb Rubber Modifier and Graphite Nanoplatelet for Pellet Asphalt Production

Abstract: The purpose of this research was to promote the recycling of pellet asphalt with Crumb Rubber Modifier (CRM) and Graphite Nanoplatelet (GNP) in pothole restoration. In this study, several laboratory tests were carried out on mixes containing CRM content ratios of 5%, 10%, and 20% and GNP content of 3% and 6% in order to identify the ideal mixing ratio of pellet-type asphalt paving materials. The Marshall stability test, the Hamburg wheel tracking test, and the dynamic modulus test were all performed to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In bitumen and asphalt modification, nanotechnology has also shown promising improvements. Nano-silica [4], nano-rubber [5], nano-clays [6], and carbon-based nanoparticles are the majority of the nanomaterials investigated and projected in the asphalt industry [7,8]. It has been demonstrated that using nano-clays with styrene-butadiene-styrene (SBS) polymer-modified bituminous binders can improve the aging resistance and the storage stability of SBS polymer-modified asphalts binders [9].…”
Section: Introductionmentioning
confidence: 99%
“…In bitumen and asphalt modification, nanotechnology has also shown promising improvements. Nano-silica [4], nano-rubber [5], nano-clays [6], and carbon-based nanoparticles are the majority of the nanomaterials investigated and projected in the asphalt industry [7,8]. It has been demonstrated that using nano-clays with styrene-butadiene-styrene (SBS) polymer-modified bituminous binders can improve the aging resistance and the storage stability of SBS polymer-modified asphalts binders [9].…”
Section: Introductionmentioning
confidence: 99%
“…One promising approach is the use of polymer-modified asphalt binders [10,24,25], which can enhance the mechanical properties of the mixture, such as stiffness, strength, and resistance to deformation [26,27]. The addition of crumb rubber powder from waste car tires and epoxy resin has also been investigated to further improve the properties of the mixture [25,28,29]. Recent research has confirmed the feasibility of crumb rubber application into the asphalt concrete for sustainability development purposes [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Pellet asphalt technology and pellet material in asphalt production, a relatively new development in the field of road construction and pavement maintenance, has garnered significant attention in recent years. This innovative technology involves the production of compacted asphalt pellets using a combination of asphalt binder and aggregate materials [32]. These pellets are designed to be easy to handle, transport, and store, offering numerous advantages over traditional hot mix asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study conducted by investigated the energy savings achieved during the manufacturing and application processes of asphalt pellets. The results suggest a substantial reduction in energy consumption compared to hot mix asphalt, contributing to a more sustainable approach [32]. Furthermore, research by Sahebzamani and colleagues explored the workability and compaction characteristics of pelletized materials in asphalt [33].…”
Section: Introductionmentioning
confidence: 99%